Kinetic study on photobiodegradation of phenol using Aspergillus Niger and N-S-TiO2 photocatalyst under visible light - Mohammed Rodzi, Amir Ridwan (2015)
The effect photodegradation by N-S doped TiO2 photocatalyst, biodegradation by Aspergillus niger and combined photo-biodegradation of phenol were investigated. The photocatalyst materials were prepared by using sol gel method with titanium isopropoxide as precursor with N-S doping by thiourea and ammonia nitrate. For photodegradation, the parameters studied were N-S-TiO2 photocatalyst dopant concentrations: 0.5%, 0.75%, 1.0% and catalyst loading: 1 g/L, 2 g/L, 3 g/L. For biodegradation, the parameter studied was the inoculum size: 10% inoculum size and 15% inoculum size. Lastly, the ideal initial phenol concentration feasible for this process was studied by varying at 10 ppm, 25 ppm and 50 ppm. As a result, the optimum parameters were: 1.0% doped N-S-TiO2 with catalyst loading of 2.0 g/L for the photodegradation, 10% inoculum size of Aspergillus niger culture for the biodegradation and in photo-biodegradation, the optimal initial concentration of phenol that should be initialized at 10 ppm phenol concentration.